A comparative study of health, nutritional status, and dietary pattern of primary school going and dropout slum children in Dhaka City, Bangladesh - Yeasmin, Sharmina; Islam, Khaleda (Asian Journal of Medical Sciences, 2016)
Background: Health affects not only current well being and future outcomes at individual and society level but also directly reflect the efficiency of health care system and the influence of surrounding environment. This is especially nutritional status of primary school age children which influence their health, dietary habit, cognition and educational achievement. Aims and Objectives: The purpose of this study was to find and compare primary school going and dropout slum children (6-12 years) regarding their health, nutritional status and dietary pattern in four selected slums in Dhaka city, Bangladesh. Materials and Methods: It was a descriptive cross-sectional study conducted among 100 children. Nutritional status was measured by collecting anthropometric data (height and weight) using standard techniques and analyzed according to WHO guidelines Result: Based on WHO standard mean of Body Mass Index (BMI), the prevalence of underweight was higher among school dropout group (76%) than school going group (54%). A statistically significant difference between two groups were found regarding prevalence of stunting (P-value=0.03) and their daily dietary habits, such as, pulses (P-value=0.007), rice, fruits, milk, and meat (P-value=0.00) and fish (P-value=0.002). This study also found that parent’s education, family size, mother’s occupation, and economic status of family have an important impact on children’s education and their nutritional status. Conclusion: Low education levels are linked to poor health and low quality dietary pattern. Lower socioeconomic condition and poor knowledge of parent’s about child education and nutritional diet makes this situation more worse. Asian Journal of Medical Sciences Vol.7(4) 2016 59-63